Analysis Of The Implementation Of Sharia Hospital In Bogor City Based On DSN MUI Law And Fatwa : (Case Study Of Bogor Islamic Hospital) - Kusumadewi, Nila Ayu; Tanjung, Hendri; Supriyanto, Trisiladi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
Indonesia is the country with the largest Muslim population in Southeast Asia, with the enactment of DSN-MUI Fatwa Number 107 of 2016 concerning the Implementation of Hospitals Based on Sharia Principles with binding provisions therein which are sharia-certified by MUKISI (All-Indonesian Health Effort Council). Law number 33 of 2014 on Halal Product Guarantees states that goods and services related to food, beverages, medicines, cosmetics, products, chemicals, biological products, genetically engineered products, as well as consumer goods that are used, utilized or utilized by the public. It is also stated that halal products are products that have been declared halal in accordance with Islamic law. This research was conducted descriptively using a mixed qualitative method to analyze the implementation of Sharia hospitals at the Bogor Islamic Hospital and quantitatively using SWOT analysis to analyze to support management in making decisions in the marketing sector. The conclusion of this study states that the management of the Bogor Islamic Hospital has fulfilled the Sharia compliance aspect referring to DSN-MUI Fatwa Number 107 of 2016 and has met halal standards in accordance with Law Number 33 of 2014. And there are results of IFAS factor analysis with a total weight value of 1 with a score of +0.71 and the EFAS factor with a total weight value of 1 with a score of +0.21. These results show that the Bogor Islamic Hospital is in quadrant 1 which means a fast growth strategy, meaning it has good opportunities and strengths.